Health at risk in immigration detention facilities - Kotsioni, I; Ponthieu, A; Egidi, S (Refugee Studies Centre, University of Oxford, 2013)
Since 2004 Médecins Sans Frontières (MSF) has provided medical and psychosocial support for asylum seekers and migrants held in different immigration detention facilities across Europe (in Greece, Malta, Italy and Belgium) where the life, health and human dignity of vulnerable people are being put at risk.